An Integrated BIM–GIS Method for Planning of Water Distribution System - Linlin Zhao; Zhansheng Liu; Jasper Mbachu (ISPRS International Journal of Geo-Information, 2019)
An important function of a water distribution system (WDS) is to supply drinking water to each demand point using a pipe network that has minimal impact on the surroundings. To produce a reliable WDS, planning usually requires a significant amount of geo-spatial information. Current planning practices for pipeline systems, which gather geographic information based on maps, are time-consuming and cumbersome. With the rapid developments in computer and information technology, it is necessary to propose a new WDS planning method that enhances the current planning practices and facilitates the decision-making process. The proposed method allows project information in building information modeling (BIM) to be incorporated into a geographic information system (GIS) model, using semantic mapping to incorporate WDS project data and geo-spatial information to facilitate the WDS planning process. Moreover, a 3D visualization model of the proposed WDS project and its surroundings is provided. In addition, topological rules are set to identify any conflicts between the WDS project and its surroundings. A real WDS project was used to validate the method. The proposed method can help project participants better understand the WDS project and its surroundings and identify any errors in the planning process, thus improving sustainable development.